Civil Service Management and Administrative Systems in South Asia - Dhakal, Tek Nath; Jamil, Ishtiaq; Paudel, Narendra Raj (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book examines public administration in South Asia in the context of rapid changes and modernization of administrative traditions, thoughts, and practices. The existing literature has, however, not given adequate attention to these developments, at least in a single volume. The book describes both the shared administrative traditions of Bhutan, Bangladesh, China, India, the Maldives, Nepal, Pakistan, and Sri Lanka, and how far they have adapted their administrative systems to respond to contemporary administrative and governance challenges. The book studies how national civil service reforms have been carried out in each member state of South Asia and how the national civil service acts and different regulations are being implemented, as well as what are the critical factors associated with the implementation of national civil service acts and reform measures in the region. Ishtiaq Jamil is Associate Professor in the Department of Administration and Organization Theory at the University of Bergen, Bergen, Norway. Tek Nath Dhakal is Professor and Head of the Department of Public Administration, Tribhuvan University, Nepal. Narendra Raj Paudel is Lecturer in the Department of Public Administration, Tribhuvan University, Nepal.